Structure and sequence variation of the genes encoding the polymorphic, immunodominant molecule (PlM), a candidate diagnostic antigen of Theileria parva - Toye, Philip G.; Gobright, E.I.; Nyanjui, J.; Nene, Vishvanath M.; Bishop, Richard P. (1995)
Initial comparison of 2 polymorphic, immunodominant molecule (PIM) cDNA sequences from Theileria parva suggested that the PIM genes consist of conserved 5' and 3' termini flanking a central variable region. Further evidence is presented, based on sequence analysis, supporting this general structure for the PIM genes. Evidence is also presented for a single copy of the PIM gene per haploid genome, implying that the different versions of PIM are encoded by distinct alleles. The central variable region of the PIM allele from the T. parva (Marikebuni) stock was found to contain 13 copies of the tetrapeptide repeat Gln-Pro-Glu-Pro. Point mutations were also detected in the 5' and 3' termini of the PIM alleles, including regions recognized by the neutralizing and typing MAb. This contrasted with the high sequence conservation of the 2 introns of the genes, suggesting that the protein is undergoing rapid evolution. Sequence comparison of PIM genes from buffalo- and cattle-derived parasites supported earlier results that the parasites infecting buffaloes constitute a more heterogeneous population than those from cattle.